COMMUNITY SCREENING OF STROKE RISK FACTORS AMONG PRODUCTIVE AGE POPULATION - Maharani, Citra; Shafira, Nyimas Natasha Ayu; Puspasari, Anggelia; Enis, Rina Nofri; Iskandar, Mirna Marhami (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Stroke is a neurological disease caused by multiple risk factor and can be prevented through early screening and lifestyle modifications. However, the misconception that stroke only affects the elderly leads to low screening interest among younger adults. This community service activity aimed to screen for stroke risk factors, particularly lipid profile examination among the productive age population in the working area of Simpang Sungai Duren Public Health Center. A total of 90 respondents aged 19-59 years participated, most of whom were office workers with sedentary lifestyles and unhealthy dietary habits. The screening included blood pressure measurement, body mass index assessment, total cholesterol and Low-Density Lipoprotein (LDL) levels. All respondents fasted for 8-10 hours before venous blood sampling. Screening results were delivered along with individual consultation and lifestyle education. The results revealed that 20% of respondents had hypercholesterolemia, 22% had elevated LDL levels, 23.26% had hypertension, 21% were overweight, and 39% were obese. These findings indicate that individuals in the productive age group may already have stroke risk factors despite being asymptomatic. Therefore, regular screening from early adulthood is essential as a primary prevention strategy against stroke.